Study Program Selection Recommendation System Using the Fuzzy Inference System Mamdani - Abdullah Muadz Nadzir Azhar; Deden Pradeka; Devi Aprianti Rimadhani Agustini (APIC, 2024)
This study presents a recommendation system for selecting study programs using the Mamdani fuzzy inference system. With the aim of assisting prospective students in making informed decisions, the system evaluates various factors including talents, UTBK scores, and school exam grades. The research utilizes the Temu Bakat test to assess talents and applies fuzzy logic to map inputs to outputs. Fuzzy rules are formulated based on the evaluation of antecedents, and aggregation combines multiple rules into a single output. Defuzzification converts fuzzy outputs into clear recommendations. The system's effectiveness is demonstrated through testing on students at UPI Campus in Cibiru, resulting in personalized study program recommendations for each student.